131 The increasing racial disparity of uterine carcinosarcoma over 16 years: a study of 35, 000 patients. (13th November 2020) - Liao, C; Richardson, M; Tran, K; Chan, C; Mann, AK; Maxwell, GL; Hamilton, CA; Tian, C; Darcy, KM; Kapp, DS; Chan, JK
Abstract : Objective: To evaluate the racial disparities of uterine carcinosarcoma based on incidence and trends in the United States. Methods: From 2001 to 2016, incidence rates were estimated from the United States Cancer Statistics after correcting for hysterectomy and pregnancy prevalence from the Behavioral Risk Factor Surveillance System (BRFSS). SEER*Stat and Joinpoint regression were used to calculate the incidence rate (per 100, 000) and average annual percent change (AAPC). Results: Of 35, 524 patients with carcinosarcoma, 66% were White, 24% Black, 7% Hispanic, and 3% Asian. Between 2001 and 2016, the overall incidence increased from 2.7 to 3.5, with an average annual percent change (AAPC) of 1.5% (p<0.001). Black women had a 3 fold higher incidence at 9.9 per 100, 000 compared to 2.8 in Whites. Additionally, Black women had a higher annual increase at 2.4% vs. 1.1% in Whites. With respect to age, patients aged 75–79 had the highest incidence at 15.5. To identify a group of patients at highest risk using demographic factors, we found the intersectionality of Blacks aged 70–74 years had an incidence of 43.2/100, 000 with an increase of 2.2% annually (p<0.001). Conclusion: Black women had a 3.5-fold higher incidence of uterine carcinosarcoma as compared to Whites. The rate of carcinosarcoma diagnosis is increasing for higher-risk populations, such as Black and older women.